2023
DOI: 10.1002/adhm.202203361
|View full text |Cite
|
Sign up to set email alerts
|

Bone‐Targeted Exosomes: Strategies and Applications

Abstract: As the global population ages, bone-related diseases have increasingly become a major social problem threatening human health. Exosomes, as natural cell products, have been used to treat bone-related diseases due to their superior biocompatibility, biological barrier penetration, and therapeutic effects. Moreover, the modified exosomes exhibit strong bone-targeting capabilities that may improve efficacy and avoid systemic side effects, demonstrating promising translational potential. However, a review of bone-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 152 publications
0
11
0
Order By: Relevance
“…Our team also proposed the concept of bone‐targeted biomaterial strategy for osteoporotic bone repair (Ren et al., 2022). Natural or engineered EVs exhibit strong bone‐targeting capabilities and become promising therapeutic approaches for orthopaedic diseases (Wang et al., 2023). Although we have verified the great in vivo targeting ability of CXCR4 + BEVs (Liu et al., 2023) and CXCR4 + MEVs (Hu et al., 2021), we further investigated the in vivo distribution of BEVs‐BC in the presence of BMP‐2 expression.…”
Section: Resultsmentioning
confidence: 99%
“…Our team also proposed the concept of bone‐targeted biomaterial strategy for osteoporotic bone repair (Ren et al., 2022). Natural or engineered EVs exhibit strong bone‐targeting capabilities and become promising therapeutic approaches for orthopaedic diseases (Wang et al., 2023). Although we have verified the great in vivo targeting ability of CXCR4 + BEVs (Liu et al., 2023) and CXCR4 + MEVs (Hu et al., 2021), we further investigated the in vivo distribution of BEVs‐BC in the presence of BMP‐2 expression.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, some cell-derived exosomes have natural targeting properties. Song et al found that endothelial cell-derived exosomes have a natural bone-targeting effect, while some other exosome-based materials also showed bone-targeting ability. , Our research also found that compared to BMSC-derived exosomes, HUVEC-Exos have stronger bone-targeting capabilities and are nontoxic, making them an ideal natural bone-targeting nanomaterial. Subsequent orthopedic research can further explore the use of this material for the treatment of bone-related diseases such as OP, fractures, and bone defects.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, EVs have attracted a lot of attention for CFTs [ 188 ], which can be isolated from human cells, body fluids, milk, bacteria, etc. [ 189 , 190 , 191 ].…”
Section: Implications Limitations and Futurementioning
confidence: 99%